Cooperative transport enabling fast Li-ion diffusion in Thio-LISICON Li10SiP2S12 solid electrolyte. (August 2019) - Zhang, Bingkai; Yang, Luyi; Wang, Lin-Wang; Pan, Feng
Abstract: LISICON-like materials are attracting attention as promising new Li-ion conductors with potential use in all-solid-state Li-ion batteries. Although the concept of cooperative diffusion mechanism has been discussed before, a detail understanding of the diffusion process is still lacking for this material. Here, an atomic-scale investigation of the Li10 SiP2 S12 (LSPS)-based system using advanced simulation techniques provides valuable insights into its Li-ion conducting mechanisms. We find that Li-ion conduction in LSPS occurs through a concerted motion of interstitial and lattice Li-ions, evidenced both from molecular dynamics trajectory analysis and energy barrier calculations. The cause for the cooperative migration is the existence of a low-barrier step, by which one Li-ion's migration helps another adjacent Li-ion's migration through mutually beneficial S atoms relaxation and electrostatic interaction. Cooperative migration occurs in the channels formed by connected LiS4 tetrahedrons through Li–Li interaction as well as dual-Li-sites. Cl-doping can enhance cooperative migration by a new low-barrier step due to more flexible PS3 Cl and large oscillation of Li, which smoothes Li potential energy surface and enhances cooperative migration. Graphical abstract: Image 1 Highlights: Using atomic-scale simulation, Li-ion conduction in LSPS occurs through cooperative transport. Cooperative transport arises from a low-barrier step because of dual-Li-sites. Metastable structure smoothes the energy profile of Li-ions. Cl-doping enhances cooperative migration by low-barrier step due to more flexible PS3 Cl.